PENGARUH STRUKTUR AKTIVA, PELUANG PERTUMBUHAN DAN KEBIJAKAN UTANG TERHADAP NILAI PERUSAHAAN - Divianto Ahmad Riyadi; Muhammad Ridwan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research aims to determine and examine the influence of Asset Structure, GrowthOpportunities and Debt Policy on Firm Value in banking sub-sector companies listed onthe Indonesia Stock Exchange for the 2018-2022 period. The population is 46 companies.The sample determination method used purposive sampling, obtained 11 companies witha research period of 5 years so that the total research sample was 55. This research usedsecondary data sourced from company financial reports as data or research objects andtested hypotheses using E-views 9 software. as a test. The research results show thatpartially the Asset Structure has no effect on Firm Value, Growth Opportunities have noeffect on Firm Value and Debt Policy has no effect on Firm Value. Simultaneous testingof Asset Structure, Growth Opportunities and Debt Policy has no effect on Firm Value.